Nest site selection and the time of breeding by Slavonian Grebes Podiceps auritus in Scotland - Summers, Ron W; Mavor, Roddy A (Wildfowl, 1998)
Bottle Sedge Carex rostrata provided the main nesting habitat of Slavonian Grebes in Scotland. In the sedge beds, the sedge density decreased and water depth increased from land to open water. The grebes preferred to nest in dense sedges growing at a medium water depth. Thus, there was an optimum mid-band of suitable sedges which provided sufficient cover, security from predators and shelter from wave action. Sedge beds did not provide good cover until early June. The observation of early nests in stands of dead reeds (mean first egg date 14 May) and in the semi-submerged branches of willows (29 May), compared with nests in sedges (6 June), suggests that the late growth of sedges limited the timing of breeding of the grebes. The average dates of first eggs for initial clutches in all nests were 5 June in 1992 and 3 June in 1993.